Physiologically based modeling in the development of novel drugs: Digital window to drug’s journey through the body - Cvijić, Sandra (Archives of Pharmacy, 2022)
The application of computer-based (in silico) modeling&simulation tools has become a global trend in different areas of science, including pharmaceutical sciences. These methods have been increasingly used in different phases of formulation development, starting with defining a sound formulation strategy, through the selection of drug dose and optimal formulation for clinical studies, to the prediction of drug absorption/disposition in different populations, identification of potential drug-drug interactions, prediction of bioequivalence study outcomes and justification of biowaivers. In silico tools for the prediction of drug bioperformance incorporate the so called physiologically-based models i.e., systems of data on physiological conditions and processes a drug undergoes in the organism, with an adequate mathematical background to describe these processes. As such, these models allow prediction of the expected therapeutic outcomes following drug administration, and offer a distinctive opportunity to test hypotheses and identify the underlying mechanisms responsible for the phenomena a drug undergoes in vivo. In other words, they act as a digital window to “drug’s journey through the body”. Physiologically-based models have been upgraded continuously, and relatively simple models evolved into the model-based drug development platforms, initiating a transformational change in drug formulation research&development. Opposed to the traditional “trial&error” methods, the outcomes of in silico modeling are based on the knowledge of in vivo processes, and planning of the optimal formulation strategy depending on drug biopharmaceutical properties and physiological characteristics of the target population. The selected examples will demonstrate the basic principles of in silico modeling in the development of pharmaceutical formulations.